2020
DOI: 10.1136/rapm-2019-100895
|View full text |Cite
|
Sign up to set email alerts
|

Motor-sparing effect of iPACK (interspace between the popliteal artery and capsule of the posterior knee) block versus tibial nerve block after total knee arthroplasty: a randomized controlled trial

Abstract: Background and objectiveAn ultrasound-guided anesthetic technique targeting the interspace between the popliteal artery and capsule of the posterior knee (iPACK) can provide posterior knee analgesia with preserved motor function after total knee arthroplasty (TKA). This study compared the peroneal nerve motor-sparing effects of iPACK block and tibial nerve block (TNB) when combined with local infiltration analgesia (LIA) and continuous adductor canal block (CACB).MethodsIn this study, 105 patients scheduled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 26 publications
6
50
0
4
Order By: Relevance
“…The search strategy identified 2180 unique citations. After independent and duplicate screening by two authors (RSD and BL), eight RCTs 13,[25][26][27][28][29][30][31] were identified that fulfilled eligibility criteria. Collectively, these eight RCTs consisted of 777 patients (377 patients received the iPACK block; 400 patients in the control cohort received another modality of peripheral nerve blockade or PAI for knee analgesia).…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search strategy identified 2180 unique citations. After independent and duplicate screening by two authors (RSD and BL), eight RCTs 13,[25][26][27][28][29][30][31] were identified that fulfilled eligibility criteria. Collectively, these eight RCTs consisted of 777 patients (377 patients received the iPACK block; 400 patients in the control cohort received another modality of peripheral nerve blockade or PAI for knee analgesia).…”
Section: Search Resultsmentioning
confidence: 99%
“…All eight RCTs 13,[25][26][27][28][29][30][31] generally demonstrated a low risk of bias in random sequence generation and allocation concealment, blinding of outcome assessment, incomplete outcome data, and selective reporting. In terms of blinding of participants, some RCTs 13,25,26 displayed a high risk for bias because although they blinded all surgeons, recovery room and floor nurses, research assistants, statisticians, and patients, it was impossible to blind the anesthesiologist performing the ultrasound-guided iPACK block who may have participated in the study. Furthermore in one study, 13 operating room nurses provided the local anesthetic medication to the anesthesiologist based on the type of regional block and thus were also not blinded.…”
Section: Risk Of Bias and Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations